(untitled) - Schalock, Robert L (New York, 2001)
Outcome-based evaluation continues to play a central role in the larger field of policy analysis and speaks to the needs and interests of administrators, students, policymakers, funders, consumers, and educators. In a thoroughgoing revision of the first edition of this classic text and reference, published by Plenum in 1995, the author broadens the coverage from his previous emphasis on developmental disabilities to include other areas of human and social service delivery such as education, health, mental health, aging, substance abuse, and corrections (Publisher description)
Keywords: Phục vụ con người,Human services,Evaluation research (Social action programs),Nghiên cứu về đánh giá (chương trình hoạt động xã hội); Đánh giá,Evaluation,Methodology; Phương pháp